Observer-based Event-triggered Predictive Control under DoS Attacks - Yang, Xiuping; Peng, Chen (Chinese Control Conference, 2021)
This paper deals with the observer-based event-triggered predictive control problem for networked control systems (NCSs) subject to state unmeasurable and packet loss induced by DoS attacks. First, a switching observer is introduced to reconstruct the state of the system, meanwhile, an event generator is designed to reduced communication pressure. Second, in order to compensate for the triggered packet loss caused by the attacks, an observer-based predictive controller is designed. Then, by constructing an appropriate Lyapunov functional, sufficient conditions are obtained to ensure the exponential stability of the closed-loop system. Finally, a numerical example is given to demonstrate effectiveness of the proposed control strategy.